2010
DOI: 10.1177/0146167210379112
|View full text |Cite
|
Sign up to set email alerts
|

Organization of Parent Knowledge: Compartmentalization and Integration in Adult Child-Parent Relationships

Abstract: Previous research has demonstrated an association between structure of beliefs about romantic partners and feelings for that partner. Here, the structure of college students' beliefs about their parents was linked to distinct types of ongoing parent-child relationships identified by cluster analysis. An integrative structure of mother knowledge was associated with an evaluatively complex type of relationship ("dealing"), characterized by greater liking and closeness and less cooperation and contact. Positive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…To the extent that the most positive self‐aspects are the most important, a person's self‐structure is described as positively integrative; if the most negative self‐aspects are most important, then a person's self‐structure is negatively integrative. In support of the basic model of compartmentalization, multiple studies have found baseline correlations between self‐structure and global mood or self‐esteem, such that positively compartmentalized individuals report more positive mood and higher self‐esteem than do positively integrative individuals, whereas negative integratives have less negative mood and higher self‐esteem than do negatively compartmentalized individuals (e.g., Ditzfeld & Showers, ; Limke & Showers, ; Showers, ; Showers & Kevlyn, ; Showers & Kling, ).…”
Section: Comparison To Relevant Models Of Self‐esteemmentioning
confidence: 94%
“…To the extent that the most positive self‐aspects are the most important, a person's self‐structure is described as positively integrative; if the most negative self‐aspects are most important, then a person's self‐structure is negatively integrative. In support of the basic model of compartmentalization, multiple studies have found baseline correlations between self‐structure and global mood or self‐esteem, such that positively compartmentalized individuals report more positive mood and higher self‐esteem than do positively integrative individuals, whereas negative integratives have less negative mood and higher self‐esteem than do negatively compartmentalized individuals (e.g., Ditzfeld & Showers, ; Limke & Showers, ; Showers, ; Showers & Kevlyn, ; Showers & Kling, ).…”
Section: Comparison To Relevant Models Of Self‐esteemmentioning
confidence: 94%
“…Both of these goals (accuracy, vigilance) might be especially valuable to individuals who need to predict when a partner might engage in behavior that is stressful for the relationship and potentially problematic for those individuals (cf. Graham & Clark, 2007;Limke & Showers, 2010). framed in this utilitarian manner, we suggest that these differing mental representations of relationship partners have differential utility for high self-monitors and low self-monitors.…”
Section: Partner Knowledge Structuresmentioning
confidence: 70%
“…as we suggested previously, these knowledge structures apparently serve this very function for low self-monitors. Conversely, individuals may utilize integrated partner knowledge structures to insure that evaluations of and reactions to partners are accurate-perhaps especially with respect to negativity in their partners (Graham & Clark, 2007;Limke & Showers, 2010). We believe that this is the goal high self-monitors are hoping to achieve using such knowledge structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, because most individuals place their children's needs, but not their partner's, above their own (Clark & Mills, 2012), they may be especially likely to experience their child's outcomes as their own and thus protect their positive child evaluations regardless of overlap. Furthermore, because parent-child relationships are more difficult to end than romantic relationships, parents may also be motivated to maintain positive child perceptions to foster more positive parent-child relationships (Limke & Showers, 2010).…”
Section: Studymentioning
confidence: 99%